2013
DOI: 10.1175/jhm-d-13-074.1
|View full text |Cite
|
Sign up to set email alerts
|

World’s Greatest Observed Point Rainfalls: Jennings (1950) Scaling Law

Abstract: The observed relation of worldwide precipitation maxima P versus duration d follows the Jennings scaling law, P ' d b , with scaling coefficient b ' 0.5. This scaling is demonstrated to hold for single-station rainfall extending over three decades. A conceptual stochastic rainfall model that reveals similar scaling behavior is introduced as a first-order autoregressive process [AR(1)] to represent the lower tropospheric vertical moisture fluxes, whose upward components balance the rainfall while the downward c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
0
12
1
Order By: Relevance
“…Maxima rainfall intensities for larger than 0.25° × 0.25° resolutions show that rainfall declines as the spatial scale becomes coarser although not by a factor of two or three (as it is between 1 m 2 and 625 km 2 ), but rather than by a factor ranging between ∼2 (for short durations) and ∼1.1 (for long durations). When the Jennings law is compared between gauges and 1° × 1° cells, the difference is never greater than 5 times, which is less than those reported by a numerical model (Zhang et al , ). The fact that extreme rainfall intensity from gauges can be two to three times greater than measurements from satellites can be explained by the poor ability of satellites to capture extreme events characterized by short‐term but heavy rainfall intensity rates.…”
Section: World's Greatest Precipitation Totals For Different Durationcontrasting
confidence: 58%
See 4 more Smart Citations
“…Maxima rainfall intensities for larger than 0.25° × 0.25° resolutions show that rainfall declines as the spatial scale becomes coarser although not by a factor of two or three (as it is between 1 m 2 and 625 km 2 ), but rather than by a factor ranging between ∼2 (for short durations) and ∼1.1 (for long durations). When the Jennings law is compared between gauges and 1° × 1° cells, the difference is never greater than 5 times, which is less than those reported by a numerical model (Zhang et al , ). The fact that extreme rainfall intensity from gauges can be two to three times greater than measurements from satellites can be explained by the poor ability of satellites to capture extreme events characterized by short‐term but heavy rainfall intensity rates.…”
Section: World's Greatest Precipitation Totals For Different Durationcontrasting
confidence: 58%
“…As noted by Field and Shutts (), several studies have suggested that the distribution of rainfall responds to the local concentration of water and energy. Such phenomenon seems to follow a fractal‐type attenuation process as the spatial scale decreases and, as shown by Zhang et al (), the Jennings law is not the exception.…”
Section: World's Greatest Precipitation Totals For Different Durationmentioning
confidence: 99%
See 3 more Smart Citations